PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA PADA UMKM MAKANAN DI KECAMATAN BANGIL : STUDI KUALITATIF BERBASIS KEARIFAN LOKAL - anwar, khoirul (Institut Teknologi dan Bisnis Yadika, 2025)
This study aims to describe and analyze Human Resource Management (HRM) practices in food MSMEs in Bangil District, influenced by local wisdom values. The research approach used was a qualitative case study. The informants consisted of MSME owners and employees. Data collection techniques were conducted through in-depth interviews, observation, and documentation. Data analysis employed an interactive model that included data reduction, data presentation, and conclusion drawing. The results indicate that HRM practices in food MSMEs in Bangil District are informal, flexible, and based on the values ​​of family, trust, and mutual cooperation. These practices represent both a strength and a challenge in improving the professionalism of HR management.